Pengaruh Manajemen Sistem Informasi Terhadap Kinerja Operasional dan Pelayanan Pelabuhan (Studi pada Pelabuhan Parepare) - Mashudi Gani; Muhammad Arsyad; Djunaidi Djunaidi; Muhammad Afdal (Journal of Innovative and Creativity, 2026)
The development of information technology encourages ports to improve operational effectiveness and service quality through the implementation of information system management. However, Parepare Port still faces obstacles in data integration, limited human resource competency, and some service processes that are still carried out manually. This study aims to analyze the influence of information system management on operational performance and port services. The research method used a quantitative approach with an associative design, involving all 54 permanent employees through a saturated sampling technique. Data were collected through questionnaires and analyzed using simple linear regression after undergoing validity, reliability, and classical assumption tests. The results showed that information system management had a positive and significant effect on operational performance with a regression coefficient of 0.779 (p = 0.000), and a positive and significant effect on port services with a regression coefficient of 0.841 (p = 0.000). These findings indicate that improving information system management can accelerate work processes, improve data accuracy, strengthen inter-unit coordination, and improve service quality to service users. In conclusion, information system management plays an important role in supporting operational efficiency and improving service quality at Parepare Port. Optimizing information systems, improving human resource competencies, and strengthening digital infrastructure are key to driving sustainable port service performance and quality.